The changing role of the hospital in European health systems - McKee, Martin; Merkur, Sherry; Edwards, Nigel; Nolte, Ellen (Cambridge University Press, 2020)
Hospitals today face a huge number of challenges, including new patterns of disease, rapidly evolving medical technologies, ageing populations and continuing budget constraints. This book is written by clinicians for clinicians and hospital managers, and those who design and operate hospitals. It sets out why hospitals need to change as the patients they treat and the technology to treat them changes. In a series of chapters by leading authorities in their field, it challenges existing models, reviews best practice from many countries and presents clear policy recommendations for policymakers and hospital administrators. It covers the main patient groups and conditions as well as those departments that make modern effective care possible, in imaging and laboratory medicine. Each chapter looks at patient pathways, aspects of workforce, required levels of specialisation and technology, and the opportunities and challenges for optimising the delivery of services in the hospital of the future. Hospitals must change in the face of changing technologies and patient needs. This book is written by clinicians who work in hospitals and know them best and is designed for hospital professionals, giving them the evidence they need to call for change, and for policy-makers and planners charged with designing and operating hospitals now and in the future.
European Observatory on Health Systems and Policies Series
Keywords: Hospital Administration; Quality of Health Care; Hospitals; poskytování zdravotní péče; reforma zdravotní péče; veřejné zdravotnictví; řízení nemocnice; Delivery of Health Care; Europe; Evropa; nemocnice; kvalita zdravotní péče; Health Care Reform